Globalization, Growth, and Distribution : Framing the Questions - Kanbur, Ravi (World Bank, Washington, DC, 2017)
In the last two decades, across a range of countries high growth rates have reduced poverty but have been accompanied by rising inequality. This paper is motivated by this stylized fact, and by the strong distributional concerns that persist among populations and policy makers alike, despite the poverty reduction observed in official statistics where growth has been sufficiently high. This seeming disconnects frames the questions posed in this paper. Why the disconnect, and what to do about it? It is argued that official poverty statistics may be missing key elements of the ground level reality of distributional evolution, of which rising inequality may be an indirect indicator. Heterogeneity of population means that there may be significant numbers of poor losers from technical change, economic reform and global integration, even when overall measured poverty falls. In terms of actions, attention is drawn to the role of safety nets as generalized compensation mechanisms, to address the ethical and political economy dimensions of such a pattern of distributional evolution. Addressing structural inequalities is also a long term answer with payoffs in terms of equitable growth. In terms of future analysis, diminishing returns have set in to the inequality-growth cross-country regressions literature. Further work to help policy makers should focus on: (i) new information to illuminate the disconnect; (ii) analysis and assessment of safety nets as generalized compensation mechanisms; and (iii) addressing specific forms of structural inequality related to assets, gender, and social groupings like caste or ethnicity.